Mary Thomas's dictionary of embroidery stitches - Thomas, Mary (Tunbridge Wells, Kent Search Press, 2019)
This classic reference book has achieved near-legendary status since it was first published, owing to its clear instructions and huge library of stitches. It includes full illustrated instructions for over 400 embroidery stitches, ranging from simple border and outline stitches, to filling stitches, canvas stitches and pulled fabric stitches. Scattered throughout are dozens of inspirational embroideries to show the stitches in action. Ideal for both those starting out with needlework and those more accomplished embroiderers who need inspiration for different stitches and techniques, this new, redesigned edition includes the internationally-renowned embroiderer Jan Eaton's revisions to the original text."--Provided by publisher
1
Keywords: Embroidery; Stitches (Sewing)